Survey of Impression Materials and Techniques Used in Fixed Prosthodontics among Nepalese Dentists - Pathak, Binita; Dahal, Sukriti; Khapung, Anju (Nepal Medical College Journal, 2021)
There is variation in fixed prosthodontics practice and many studies have concluded that clinicians definitely deviate from the recommended clinical protocols. If this happens during treatment with fixed prosthesis, the quality of fixed prostheses is compromised which affects it’s long term survival. Therefore, the aim of this study was to evaluate the use of impression materials and techniques in fixed prosthodontics among Nepalese dentists and to compare the findings on the basis of educational level and years of experience. A cross-sectional, questionnaire-based online survey was done amongst the Nepalese Dentists through google forms. Data from the completed questionnaires were analysed using the SPSS version 16. All statistical analyses were carried out at a significance level of P < 0.05. Out of 129 participants, 68 (52.7%) dentists often made diagnostic impression for fabrication of study cast. 85(65.9%) dentists used Addition silicone, 11(8.5%) used Condensation silicone and 33(25.6%) used Alginate for final impression making. Most commonly used elastomeric impression technique was Putty Wash single stage (56.2%), 40.7% used Putty Wash two stage, 3.1% used Single mix (Monophase) technique. Regarding retraction cord, 63.5% of dentists used Plain gingival retraction cord and 35.7% of dentists used Chemical impregnated retraction cord. Conclusion: The study found that most of the responses on use of impression materials and techniques were significantly associated with the level of education and clinical experience.